K‐RasV14I‐induced Noonan syndrome predisposes to tumour development in mice. Issue 2 (26th April 2016) - Hernández‐Porras, Isabel; Schuhmacher, Alberto J; Garcia‐Medina, Raquel; Jiménez, Beatriz; Cañamero, Marta; de Martino, Alba; Guerra, Carmen
Abstract: The Noonan syndrome (NS) is an autosomal dominant genetic disorder characterized by short stature, craniofacial dysmorphism, and congenital heart defects. A significant proportion of NS patients may also develop myeloproliferative disorders (MPDs), including juvenile myelomonocytic leukaemia (JMML). Surprisingly, scarce information is available in relation to other tumour types in these patients. We have previously developed and characterized a knock‐in mouse model that carries one of the most frequent KRAS ‐NS‐related mutations, the K ‐Ras V14I substitution, which recapitulates most of the alterations described in NS patients, including MPDs. The K ‐Ras V14I mutation is a mild activating K‐Ras protein; thus, we have used this model to study tumour susceptibility in comparison with mice expressing the classical K‐ Ras G12V oncogene. Interestingly, our studies have shown that these mice display a generalized tumour predisposition and not just MPDs. In fact, we have observed that the K ‐Ras V14I mutation is capable of cooperating with the p16Ink4a/p19Arf and Trp53 tumour suppressors, as well as with other risk factors such as pancreatitis, thereby leading to a higher cancer incidence. In conclusion, our results illustrate that the K‐Ras V14I activating protein is able to induce cancer, although at a much lower level than the classical K‐ Ras G12V oncogene, and that it can be significantly modulated by both genetic and non‐genetic events. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.